Successful return to elite sport after bilateral knee dislocations: A case report - Sonnery-Cottet, B.; Galvao Abreu, F.; Saithna, A.; Ouanezar, H.; Reina Fernandes, L.; Fayard, J.-M.; Bulle, S.; Pedron, O.; Chambat, P.; Boisgard, S. (Orthopaedic Journal of Sports Medicine, 2019)
Knee dislocations are uncommon and occur with a reported incidence of less than 0.02% of all orthopaedic injuries. These injuries are defined by complete disruption of the integrity of the tibiofemoral articulation. They are challenging injuries to manage and are associated with the risk of potentially devastating immediate and short-term complications, including popliteal artery injuries, common peroneal nerve injuries, acute compartment syndrome, and deep venous thrombosis, and controversy still exists regarding their optimal treatment. Despite the severity of these injuries, a recent systematic review has demonstrated that some level of sport participation is possible after multiligament knee injuries (MLKIs) for more than half of patients, but returning to preinjury levels of sport after surgical treatment is low, at just 22% to 33%.